Growth and nutrition of coffee seedlings influenced by replacement of potassium by sodium - Pereira Baliza, Danielle; William Ávila, Fabricio; Guedes Carvalho, Janice; José Guimarães, Rubens; Martins Abdão dos Passos, Alexandre; Alves Pereira, Vinicius (Coffee Science - ISSN 1984-3909, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->Sodium is considered a beneficial element for plants and, for some cultures, it can partially substitute potassium nutrition. However, little is known in respect of the influence of this cation on coffee plant. The present study aimed to verify the effect of the supply of sodium in substitution of potassium on the growth and nutrition of the coffee seedlings (Coffea arabica L.) cv. Acaiá Cerrado selection MG-1474. The experiment, conducted in vases with nutrient solution in a completely randomized design, was made up of seven treatments: two sodium doses (0.9 and 1.8 mM) and five substitution proportions of potassium by the sodium (0, 25, 50, 75 and 100 %). Biweekly, the plant height, stem diameter and the number of pairs of leaves was evaluated for six months. At the end of this period, the dry matter production and the contents and accumulations of sodium and nutrients in the root, stem and leaf were determined. The substitution of the potassium by the sodium in 25% of the recommended base did not interfere significantly in the development of the plants; however, that substitution starting from 50 % reduced their dry matter production. The sodium uptake by the coffee plant seedlings was, in average, 24 times lower in comparison with that of potassium. Regarding the other nutrients, the proportions of sodium interfered little in their leaf contents, except magnesium, which presented considerably high uptake efficiency in the absence of potassium. Based on the results, under the studied conditions, it was concluded that the supply of sodium does not promote a benefit to the coffee plant seedlings, enabling reduced their growth starting from 50 % of substitution of the potassium by the sodium.